Stromal Tumors of the Esophagus. Presentation of two clinical cases and Literature Review - Santiago, Pablo; Maina, Luis; Salom, Andrés; Taroco, Luis; Carriquiry, Luis (Cirugía del Uruguay, 2006)
Objetive: Clinical history of two patients with oesophagic stromal tumors. Analysis of all aspects connected with its management, both clinical and paraclinical, for the purpose of therapy.